Current status and perspectives in oxidative, non-oxidative and CO2-mediated dehydrogenation of propane and isobutane over metal oxide catalysts. (18th November 2020) - Otroshchenko, Tatiana; Jiang, Guiyuan; Kondratenko, Vita A.; Rodemerck, Uwe; Kondratenko, Evgenii V.
Abstract : Conversion of propane or isobutane from natural/shale gas into propene or isobutene, which are indispensable for the synthesis of commodity chemicals, is an important environmentally friendly alternative to oil-based cracking processes. Abstract : Conversion of propane or butanes from natural/shale gas into propene or butenes, which are indispensable for the synthesis of commodity chemicals, is an important environmentally friendly alternative to oil-based cracking processes. Herein, we critically analyse recent developments in the non-oxidative, oxidative, and CO2 -mediated dehydrogenation of propane and isobutane to the corresponding olefins over metal oxide catalysts. Particular attention is paid to (i) comparing the developed catalysts in terms of their application potential, (ii) structure–activity–selectivity relationships for tailored catalyst design, and (iii) reaction-engineering aspects for improving product selectivity and overall process efficiency. On this basis, possible directions for further research aimed at the development of inexpensive and environmentally friendly catalysts with industrially relevant performance were identified. In addition, we provide general information regarding catalyst preparation and characterization as well as some recommendations for carrying out non-oxidative and CO2 -mediated dehydrogenation reactions to ensure unambiguous comparison of catalysts developed in different studies.